ANALYSIS OF COMPLEX PHYTOCENOSES OF IRON ORE COMPANIES DUMPS OF THE KOSTANAY REGION (Experimental biology, 2023)
This article presents the results of a study of the degree of self-overgrowing of dump sites of Sokolovsko-Sarbai Mining and Processing Production Association (SSGPO) JSC and Kachary Ruda JSC at the stage of a complex phytocenosis In total, in the course of our study, 63 geobotanical descriptions were compiled, 22 of which describe complex phytocenoses, 26 - group-thicket communities, 15 - pioneer groups.  It was found that the rate of change in the stages of syngenesis and the general patterns of development of the vegetation cover, including at the stage of a complex phytocenosis, differ on saline and non-saline soils. The age of dumping has a lesser effect on the processes of flora restoration than edaphic factors. On non-saline soils, a parazonal meadow-steppe community is formed, birch-aspen plantations are formed with a small admixture of pine. On saline soils, communities form species with a wide ecological amplitude.
Keywords: complex phytocenosis; technogenic landscape; self-overgrowing of dumps; iron ore companies dumps; syngenesis